PENGARUH BUDAYA ORGANISASI, KOMPENSASI, DAN MOTIVASI MELALUI KOMPETENSI TERHADAP KINERJA PEGAWAI PT. RHB SEKURITAS INDONESIA ERA INDUSTRI 5.0 - Achmad Adrilan; Harry Indratjahyo; Suharto (Jurnal Ekonomi dan Industri, 2024)
This research aims to analyze the influence of organizational culture, compensation and motivation, through competency on the performance of PT employees. RHB Securities Industrial Era 5.0. This research was conducted on employees of PT. RHB Sekuritas Indonesia. The sampling technique used was saturated sampling technique, and used path analysis methods. The results of this research are: 1) Organizational culture directly has a significant effect on employee performance; 2) Compensation directly has a significant effect on employee performance; 3) Motivation directly has a significant effect on employee performance; 4) Competence directly has a significant effect on employee performance; 5) Competence does not interfere with organizational culture on employee performance; 6) Competency does not interfere with compensation for employee performance; 7) Competence intervenes in motivation on employee performance.